The Implementation of Academic Supervision by Madrasa Supervisors in Cianjur - Rudi Ahmad Suryadi (Tarbiyah Departement collaboration with AMCA, 2020)
This study aimed to analyze the planning and implementation of academic supervision conducted by madrasa supervisors. A qualitative approach with a descriptive method is applied to produce meaningful findings about the object under study. Data collection techniques used were interviews, documentation, and observation. Data analysis was performed with qualitative indicators. The results showed that the supervisors of madrasa in the Ministry of Religion in Cianjur had compiled an academic supervision program. Academic supervision is done by individual and group methods. The techniques applied include individual meetings, class observations, class visits, group discussions, training, and group meetings. The success of the academic supervision program is supported by the creation of a harmonious relationship between supervisors and teachers in understanding problems, obstacles, and agreeing on alternative solutions.